2005
DOI: 10.1007/s00125-005-1756-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of American Diabetes Association (2000) criteria for diagnosis of gestational diabetes mellitus in Spain

Abstract: Use of the ADA criteria to identify GDM would result in a 31.8% increase in prevalence compared with NDDG criteria. However, as the contribution of these additionally diagnosed cases to adverse GDM outcomes is not substantial, a change in diagnostic criteria is not warranted in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
3
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 39 publications
2
56
3
15
Order By: Relevance
“…Glucose intolerance or obesity was not significantly associated with PIH or macrosomia in an Australian cohort [22]. The present study, partially reported in [15], identifies pregestational BMI and abnormal glucose tolerance categories as independent predictors of perinatal outcome with similar ORs for abnormal glucose tolerance categories and upper BMI quartiles. In addition, it is important to note that upper BMI quartiles in this study do not represent extreme obesity; in fact, the cut-off for the fourth quartile is close to that of overweight.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Glucose intolerance or obesity was not significantly associated with PIH or macrosomia in an Australian cohort [22]. The present study, partially reported in [15], identifies pregestational BMI and abnormal glucose tolerance categories as independent predictors of perinatal outcome with similar ORs for abnormal glucose tolerance categories and upper BMI quartiles. In addition, it is important to note that upper BMI quartiles in this study do not represent extreme obesity; in fact, the cut-off for the fourth quartile is close to that of overweight.…”
Section: Discussionsupporting
confidence: 53%
“…All variables for which significance is provided are included in the model. Predictive models have been published in [15]. This table adds information on attributable and prevented fractions in the population gories for the prediction (and potential prevention) of macrosomia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the population-based studies, in the hospital-based studies the prevalence of GDM varied depending upon the diagnostic criteria employed in the study, whether the study was retrospective or prospective as well as the country of residence, ethnicity and racial group of the study participants. Three of the hospital-based studies directly compare GDM prevalence rates based on NDDG and C & C criteria (86)(87)(88). In these three studies, NDDG rates range from 3.2% in a study conducted in Mexico(86) to 8.8% in a study conducted in Spain(87) with corresponding C & C rates ranging from 4.1% to 11.6%(86-88).…”
Section: Hospital-based Studiesmentioning
confidence: 99%